الشغور القانوني في إجراءات المادة الأسرية دراسة موضوعية إجرائية للوساطة الصلحية في قضايا النزاعات الأسرية على ضوء القانونين (05-09) و(08-09) - سنوسي, علي (Revue jurisprudence, 2020)
في مواجهة القضايا المتلاحقة على القضاء الأسري في مختلف الجهات القضائية، وقصد إيجاد آلية قانونية فعالة مكملة للآليات الموجودة بأقل جهد وأقصر تكلفة وبأقصى فاعلية في ضمان السير الحسن لمرفق القضاء الأسري في معالجة الكم الهائل من النزاعات المعروضة عليه من جهة، وإصلاح وتأهيل لكيان الأسرة من جهة ثانية إهتدى المشرع الجزائري في ظل قانون الإجراءات المدنية والإدارية ساري المفعول رقم 08-09 المؤرخ في 23 فيفري 2008 إلى الوساطة كآلية مستحدثة من أجل تبني سياسة إجرائية تقوم على المصالحة بين طرفي عقد الزواج عندما تتعرض الأسرة إلى ما يهدد كيانها ويعرضها للخطر. الكلمات المفتاحية: النزاعات الأسرية، النقائص الإجرائية، الوساطة الصلحية، التعسف في استعمال الحق الأسري.   Abstract: In the face of successive cases of family justice in various judicial bodies, and with the aim of creating an effective legal mechanism to complement the existing mechanisms with the least effort and the lowest cost and the most effective in ensuring the proper functioning of the family justice facility in dealing with the large number of disputes before it on the one hand, and reform and rehabilitation of the family entity on the one hand Again, under the Code of Civil and Administrative Procedure Law No. 08-09 of 23 February 2008, the Algerian legislator has sought to mediate as a new mechanism for the adoption of a procedural policy based on reconciliation between the parties to the marriage contract when the family is exposed to what threatens its existence and endangers it. key words : Family disputes, procedural deficiencies, conciliatory mediation, abuse of family rights .